부착형 치주 창상 피복재가 치주수술 후 동통 및 치유에 미치는 효과에 관한 임상 연구 - 민한슬(Han-Seul Min); 강대영(Dae-Young Kang); 이성조(Sung-Jo Lee); 윤세영(Sei-Young Yun); 박정철(Jung-Chul Park); 조인우(In-Woo Cho) (Journal of dental rehabilitation and applied science, 2020)
Purpose: After periodontal surgery, studies have found that the use of periodontal wound dressing reduces the risk of wound infection and increases healing. The purpose of this study is to evaluate the effect of attachable periodontal wound dressing on the healing and patient satisfaction after periodontal flap surgery. Materials and Methods: Twenty-eight patients requiring periodontal surgery underwent periodontal flap surgery on both quadrants of maxilla or mandible. Postoperative pain, bleeding, dietary discomfort and hypersensitivity in relation to attachable periodontal wound dressing was assessed using Visual Analogue Scale (VAS). Additional survey on frequency of burning sensation and overall satisfaction rates were assessed. Results: VAS mean values for pain, bleeding, and dietary discomfort depending on the presence and absence of attachable wound dressing were; pain: 2.82, 3.96 (P = 0.002), bleeding: 1.61, 2.54 (P = 0.008), dietary discomfort: 2.82, 4.18 (P < 0.001), respectively. Test groups with attachable wound dressing reported significantly lower rates of discomfort. No significant difference was observed in burning sensation and hypersensitivity related with wound dressing. Satisfaction was higher in 75% of patients who received wound dressing. Conclusion: According to the results of this study, patients who received attachable periodontal wound dressing reported less postoperative pain, bleeding, and dietary discomfort. There was no statistical significance related to the use of wound dressing with burning sensation and hypersensitivity. 목적: 치주포대는 감염 위험을 줄이고 치유를 증대 시킨다는 연구들이 있다. 본 연구는 치주 수술 후 부착형 창상 피복재의 사용이 치유 및 수술 만족도에 미치는 영향을 평가하고자 하였다. 연구 재료 및 방법: 치주 수술이 필요한 환자 28명을 대상으로 상악 또는 하악의 양측 사분면에 치주 수술을 시행하였다. Visual Analogue Scale (VAS)를 이용해 술 후 동통, 출혈, 식이 불편감, 지각 과민을 평가하고 추가적으로 작열감과 수술 만족도에 관해 평가하였다. 결과: 수술 후 동통, 출혈, 식이 불편감에 관한 VAS 평균 값은 창상 피복재 유무에 따라 각각; 동통: 2.82, 3.96 (P = 0.002), 출혈: 1.61, 2.54 (P = 0.008), 식이 불편감: 2.82, 4.18 (P < 0.001)로 창상 피복재를 적용한 그룹에서 불편감이 적었으며, 통계적으로 유의하였다. 작열감, 지각 과민과 창상 피복재 적용 유무 사이에 유의한 차이는 없었다. 수술 만족도는 75%에서 창상 피복재를 사용한 경우 높았다. 결론: 본 연구의 결과에 따르면, 창상 피복재의 사용유무와 작열감, 지각 과민과의 통계적 유의성은 없었으나 창상 피복재를 사용한 경우 술 후 동통, 출혈, 식이 불편감이 적었다.